Integrated and Contextual Basic Science Instruction in Preclinical Education: Problem-Based Learning Experience Enriched With Brain/Mind Learning Principles - (:unkn) unknown (EDAM, 2015)
Recently, integrated and contextual learning models such as problem-based learning (PBL) and brain/mind learning (BML) have become prominent. The present study aimed to develop and evaluate a PBL program enriched with BML principles. In this study, participants were 295 first-year medical students. The study used both quantitative and qualitative methods (mixed design). First, the students' hemispheric preferences were defined using the Human Information Processing Survey and reassessed using event-related potentials (ERPs). Then, by considering BML principles, a six-week PBL program was revised and evaluated using both quantitative and qualitative tools, including evaluation forms, exam scores, expert observations, document reviews, and interviews. With regard to hemispheric preferences, 59.9% of the students preferred both hemispheres, 28.9% preferred the right, and 11.2% preferred the left, and these partially correlated with ERP P300 recordings. The evaluation study showed that compared with the standard PBL program, the students and tutors were more satisfied with the BML-enriched PBL program, and the students' average exam scores were higher and the differences were statistically significant (p < .001). These results demonstrate that various learning models can be improved using BML principles, resulting in increased satisfaction and academic success.
Keywords: Learning environment/climate; Learning process; Hemispheric preference; Program evaluation; Small-group learning; OUTCOMES CORRELATE; CRITICAL INCIDENTS; GUIDE; PERCEPTIONS; CURRICULUM; STUDENTS